2022
DOI: 10.1021/acs.biomac.2c01162
|View full text |Cite
|
Sign up to set email alerts
|

Restructuring the Interface of Silk–Polycaprolactone Biocomposites Using Rigid-Flexible Agents

Abstract: Natural fiber-reinforced biocomposites with excellent mechanical and biological properties have attractive prospects for internal medical devices. However, poor interfacial adhesion between natural silk fiber and the polymer matrix has been a disturbing issue for such applications. Herein, rigid-flexible agents, such as polydopamine (PDA) and epoxy soybean oil (ESO), were introduced to enhance the interfacial adhesion between Antheraea pernyi (Ap) silk and a common medical polymer, polycaprolactone (PCL). We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Which leads to increased spacing and reduced crystalline regions in the composite hydrogel, resulting in a more flexible membrane. Moreover, the polar bonds between the silk fibrous molecular chains are disrupted, allowing the molecular chains to slide more easily, thereby increasing the plasticity of the hydrogel 31,32 . However, if the PPG content is further increased, the PPG molecules start to form clusters, separating from the silk fibrous structure.…”
Section: Rresults and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Which leads to increased spacing and reduced crystalline regions in the composite hydrogel, resulting in a more flexible membrane. Moreover, the polar bonds between the silk fibrous molecular chains are disrupted, allowing the molecular chains to slide more easily, thereby increasing the plasticity of the hydrogel 31,32 . However, if the PPG content is further increased, the PPG molecules start to form clusters, separating from the silk fibrous structure.…”
Section: Rresults and Discussionmentioning
confidence: 99%
“…Moreover, the polar bonds between the silk fibrous molecular chains are disrupted, allowing the molecular chains to slide more easily, thereby increasing the plasticity of the hydrogel. 31,32 However, if the PPG content is further increased, the PPG molecules start to form clusters, separating from the silk fibrous structure. This disrupts the uniform system and significantly decreases the mechanical properties.…”
Section: Rresults and Discussionmentioning
confidence: 99%
“…In this regard, Zhao et al reported that incorporating polycaprolactone (PCL) into silk fibers can impact the interfacial adhesion of these biocomposites and result in properties relevant to future biomedical applications needing substrates with optimal adhesion. The high compatibility between the protein and the PCL was achieved by including natural additives such as epoxy soybean oil . The potential of altering the morphologies of protein systems by biomacromolecules was also tested by Niu et al, where carboxymethylcellulose was used to tailor the morphologies of colloidal particles from ovalbumin protein .…”
Section: Proteins As Building Blocksmentioning
confidence: 99%